2023
DOI: 10.1007/s00535-023-02033-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for venous thromboembolism in the Cancer-VTE Registry pancreatic cancer subcohort

Takuji Okusaka,
Akio Saiura,
Kazuaki Shimada
et al.

Abstract: Background This substudy of the Cancer-VTE Registry estimated venous thromboembolism (VTE) incidence and risk factors in pancreatic cancer patients. Methods The Cancer-VTE Registry was an observational study that collected VTE data from patients with solid tumors across Japan. We measured baseline VTE prevalence, and at 1-year follow-up, the cumulative incidence of symptomatic and composite VTE (symptomatic VTE and incidental VTE requiring treatment), blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 4 A Japanese nationwide multicenter observational study reported a VTE incide of 8.5% among stage II–IV PC patients with planned cancer treatment. 6 In their data, VTE prevalence was lower in other cancer types: 6.9% in stomach cancer, 6.4% in colorectal cancer, 5.5% in gynecologic cancer, 5.1% in lung cancer, and 2.0% in breast cancer. Furthermore, 1‐year cumulative VTE incidence was 3.6% among PC patients compared to 1.6% among other cancers.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… 4 A Japanese nationwide multicenter observational study reported a VTE incide of 8.5% among stage II–IV PC patients with planned cancer treatment. 6 In their data, VTE prevalence was lower in other cancer types: 6.9% in stomach cancer, 6.4% in colorectal cancer, 5.5% in gynecologic cancer, 5.1% in lung cancer, and 2.0% in breast cancer. Furthermore, 1‐year cumulative VTE incidence was 3.6% among PC patients compared to 1.6% among other cancers.…”
Section: Discussionmentioning
confidence: 87%
“… 2 , 3 , 4 In PC patients, both symptomatic and asymptomatic VTEs are common. 2 , 5 , 6 , 7 Patients undergoing chemotherapy for metastasized PC are at an even greater risk of VTE. 4 , 8 , 9 , 10 , 11 VTEs detected early following a PC diagnosis associate with a worse survival and are indicative of more aggressive tumor pathology.…”
Section: Introductionmentioning
confidence: 99%